Faunistic analysis of insects of Deva Vatala National Park and agroecosystem of Gujrat Pakistan - Muhammad Umar; Mubashar Hussain (Kuwait Journal of Science)
Insect biodiversity drives ecological functioning and provides ecosystem services in different landscapes. Protected areas with the least anthropogenic disturbances provide resources with the least disturbance in habitat favouring insect species belonging to different guilds to coexist and contribute to the ecosystem processes. Studies have highlighted the significance of anthropogenic landscapes including agricultural ecosystems for harboring rich native biodiversity. To understand the species composition and abundance agricultural landscape, we explored insect fauna in Deva Vatala National Park (DVNP), Bhimber (Azad Kashmir), and associated croplands of Gujrat, Punjab, Pakistan. We aimed to assess the abundance, richness, and diversity of the insect orders, families, and species found in the two habitats i.e. national park and croplands. Fortnightly surveys were conducted during 2017-2019. Sampling methodology consisted of handpicking, using sweep nets, light traps, and pitfall traps, and insect collection was identified by using taxonomic keys. A total of 239 insect species representing 10 orders and 69 families were collected and identified from both habitat types. For both diversity and abundance, we detected a significant difference in community composition at species, family, and order levels. Several insect orders and families demonstrated significant differences (p< 0.05) in either abundance or richness or both between the two types of habitats. Several families of Coleoptera, which contains dung beetles, ground beetles, ladybird beetles showed greater richness in DVNP. However, we also detected that several insect orders showed greater richness in the croplands of Gujrat. But we observed the pattern of the greater abundance of insect orders in DVNP. Both types of habitat can have important consequences on insect fauna having great importance in the ecosystem services and functions. Protected areas nearby associated croplands have the potential to contribute immensely to biodiversity conservation and ecosystem service provision both at the local scale and the landscape scale.